EVERY IDEA IS A GOOD IDEA : BE CREATIVE ANYTIME, ANYWHERE - Sturges, Tom. (Jeremy P. Tarcher/Penguin, 2014)
"Access a level of creativity you never thought possible, using techniques Tom Sturges-former head of creative at Universal Music Publishing Group-learned in his 25-plus years in the music industry. Everyone is innately creative. But many of us-especially those trying to develop careers in music and the arts-wish we knew how to better tap into our creative potential. Is there a way to more easily connect with the part of our minds that knows how to complete a song, finish a poem, or solve a problem? Music industry veteran Tom Sturges argues that there is. Sturges-who, in his 25-plus-year career, has worked with artists from Carole King and the Foo Fighters to the Red Hot Chili Peppers and Outkast-has developed dependable techniques to help you recognize and harness your own creative power, whenever and wherever you need it. Every Idea Is a Good Idea invites readers to find the pathway to their own creative endeavors."--